2021
DOI: 10.1016/j.atherosclerosis.2021.06.912
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the chemokine network in atherosclerosis

Abstract: Chemokines and their receptors represent a potential target for immunotherapy in chronic inflammation. They comprise a large family of cytokines with chemotactic activity, and their cognate receptors are expressed on all cells of the body. This network dictates leukocyte recruitment and activation, angiogenesis, cell proliferation and maturation. Dysregulation of chemokine and chemokine receptor expression as well as function participates in many pathologies including cancer, autoimmune diseases and chronic in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 113 publications
0
24
0
1
Order By: Relevance
“…In addition, pathways of chemokine, cytokine, and immune cells were also reflected in advanced atherosclerosis samples. Their roles have been extensively studied, which either help in atherosclerosis advancements or vice versa, blocking the cytokines and chemokines via the means of broad-spectrum inhibitors, neutralizing antibodies, application of decoy receptors, or RNA interference has been proven to be effective strategies to encumber atherosclerosis progression (31)(32)(33). Likewise, GSEA has also detected the autoimmune diseases and B cell pathway enrichments.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, pathways of chemokine, cytokine, and immune cells were also reflected in advanced atherosclerosis samples. Their roles have been extensively studied, which either help in atherosclerosis advancements or vice versa, blocking the cytokines and chemokines via the means of broad-spectrum inhibitors, neutralizing antibodies, application of decoy receptors, or RNA interference has been proven to be effective strategies to encumber atherosclerosis progression (31)(32)(33). Likewise, GSEA has also detected the autoimmune diseases and B cell pathway enrichments.…”
Section: Discussionmentioning
confidence: 99%
“…In the present study, the hsa_circ_0093708-miR-4533-AQP4 axis was predicted, and the increased level of hsa_circ_0093708 in plasma exosomes of AIS patients suggested that AIS patients may have upregulated the expression of AQP4 and, therefore, be prone to brain injury. Chemokine signaling was indispensable for leukocyte migration, which is a crucial event in the development of inflammation and atherosclerosis ( Ruytinx et al, 2018 ; Yan et al, 2021 ). In this context, we found that hsa_circ_0066867 and hsa_circ_0041685, significantly increased in AIS patients, potentially regulate chemokine signaling through miR-6737-5p-CCL2 and miR-3192-5p-CXCL12, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Six core genes were identified (FPR3, MS4A4A, C1QB, CCL18, CXCR4, and CXCL2) in the protein−protein interaction (PPI) network, three of which (CCL18, CXCR4, and CXCL2) were markedly enriched in the chemokine signaling pathway and in particular the CXCR4 and CXCL2 genes could be linked to atherosclerotic plaque progression (GSE28829 and GSE41571, [128]). Furthermore, the chemokines discussed above, CCL5, CCL19 and CXCR4, were also more present in advanced plaques versus early-stage atherosclerotic plaque [124]. Of interest, chemokine or chemokine receptor alterations during atherogenesis seem more relevant in the plaque, since no differences were observed in peripheral blood mononuclear cell (PBMC) and peripheral blood samples (GSE20129, [129]).…”
Section: Preclinical Studies: Discovering the Therapeutic Potential O...mentioning
confidence: 99%
“…Analytical tools, such as gene expression microarray and RNA sequencing, allow for the detection of alterations in gene expression in different stages of the atherogenic process. Publicly available atherosclerosis related datasets are being benefited from and knowledge has been gained on the changes in the gene expression of chemokines and chemokine receptors [124]. Accordingly, CCL5, CCL19 and CXCR4 were identified as being more highly expressed in human plaque specimens as compared to control tissue [124].…”
Section: Preclinical Studies: Discovering the Therapeutic Potential O...mentioning
confidence: 99%
See 1 more Smart Citation